1999
DOI: 10.1002/(sici)1097-4628(19991209)74:11<2667::aid-app14>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic starch/PVAl compounds: Preparation, processing, and properties

Abstract: ABSTRACT:As a renewable and native polymeric material, thermoplastic starch is gaining increased acceptance because of resource and environment concerns. This study reports the formulation design of native starch/polyvinyl alcohol (PVAl) compounds; the preparation technology to make them available for thermoplastic processing; and their rheological, mechanical, and degradation properties. Among various plasticizers investigated, a mixture of glycerin and water (50/50 wt %) is found to be the best one for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…The conventional plasticizer used for starch and PVOH composites is glycerol and water (Lawton & Fanta, 1994;Liu, Feng, & Yi, 1999), but several other chemicals like sorbitol (Park, Chough, Yun, & Yoon, 2005;Westhoff, Kwolek, & Otey, 1979), urea (Tudorachi, Cascaval, Rusu, & Pruteanu, 2000), citric acid (Park et al, 2005;Zou, Jin, & Xin, 2008), as well as complex plasticizers (Zhou, Cu, Jia, & Xie, 2009) have also been successfully employed. Liu et al (1999) compounded starch and PVOH using a single screw extruder.…”
Section: Plasticizers For Starch-pvoh Blendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional plasticizer used for starch and PVOH composites is glycerol and water (Lawton & Fanta, 1994;Liu, Feng, & Yi, 1999), but several other chemicals like sorbitol (Park, Chough, Yun, & Yoon, 2005;Westhoff, Kwolek, & Otey, 1979), urea (Tudorachi, Cascaval, Rusu, & Pruteanu, 2000), citric acid (Park et al, 2005;Zou, Jin, & Xin, 2008), as well as complex plasticizers (Zhou, Cu, Jia, & Xie, 2009) have also been successfully employed. Liu et al (1999) compounded starch and PVOH using a single screw extruder.…”
Section: Plasticizers For Starch-pvoh Blendsmentioning
confidence: 99%
“…Liu et al (1999) compounded starch and PVOH using a single screw extruder. To obtain good processability, they found that glycerol is much more effective than water as a plasticizer for the compounds, but it scarified tensile strength and water barrier properties.…”
Section: Plasticizers For Starch-pvoh Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the thermal processing of starch, the addition of plasticizer is an effective way to weaken the hydrogen bonding interactions of starch molecules, increase the molecular mobilities, reduce the melting temperatures, and modify basic starch into pseudo-thermoplastic starch (PTS) [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The developments on the production of starch=PVA blended biodegradable polymers have been reported by several authors [7][8][9][10][11][12] . The blended materials could be produced into excellent mechanical and biodegradable polymers, but the materials are not sufficiently melted by melt processing.…”
Section: Introductionmentioning
confidence: 99%